2013
DOI: 10.1177/1753193413516244
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year long-term results of total joint arthroplasties with ARPE® implant in the treatment of trapeziometacarpal osteoarthritis

Abstract: Between May 1999 and April 2002 a total of 69 consecutive thumb carpometacarpal joint arthoplasties were performed in a total of 64 patients for carpometacarpal joint osteoarthritis using the cementless hydroxyapatite (HA)-coated unconstrained ARPE implant. Clinical, functional and radiological results at 10-year follow-up are presented. Survival analysis was performed using the Kaplan-Meier method. Of the 64 patients, four were lost to follow-up, 60 implants (92.3%) were functional and five (7.7%) were not (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
60
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 25 publications
8
60
0
9
Order By: Relevance
“…Although good medium-and longterm outcomes have been reported after treatment of thumb basal joint osteoarthritis by trapeziometacarpal prosthesis and by LRTI, only 3 studies have compared these techniques. [3][4][5][6][7][8][9][10][11][12][14][15][16][17][18][19] A prospective study of 98 patients by Ulrich-Vinther et al 20 compared Elektra prosthesis (Fixano, Péronnas, France) with LRTI using the Sigfusson and Lundborg technique at 1 year postoperatively and reported faster and better pain relief, stronger grip function, greater range of motion, and lesser convalescence time with the trapeziometacarpal joint prosthesis than with the tendon interposition arthroplasty. Vandenberghe et al 21 and De Smet et al 22 compared the long-term outcomes between cemented trapeziometacarpal prosthesis (De la Caffinière; Howmedica, Newbury, United Kingdom; and Roseland; DePuy) and LRTI (Burton-Pellegrini technique) in retrospective studies of 519 and 55 patients, respectively, after a mean follow-up of 5.4 and 9 years, respectively, based on the same initial series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although good medium-and longterm outcomes have been reported after treatment of thumb basal joint osteoarthritis by trapeziometacarpal prosthesis and by LRTI, only 3 studies have compared these techniques. [3][4][5][6][7][8][9][10][11][12][14][15][16][17][18][19] A prospective study of 98 patients by Ulrich-Vinther et al 20 compared Elektra prosthesis (Fixano, Péronnas, France) with LRTI using the Sigfusson and Lundborg technique at 1 year postoperatively and reported faster and better pain relief, stronger grip function, greater range of motion, and lesser convalescence time with the trapeziometacarpal joint prosthesis than with the tendon interposition arthroplasty. Vandenberghe et al 21 and De Smet et al 22 compared the long-term outcomes between cemented trapeziometacarpal prosthesis (De la Caffinière; Howmedica, Newbury, United Kingdom; and Roseland; DePuy) and LRTI (Burton-Pellegrini technique) in retrospective studies of 519 and 55 patients, respectively, after a mean follow-up of 5.4 and 9 years, respectively, based on the same initial series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…2011), and 91% and 94% for replacement of the trapeziometacarpal (TMC) joint (Krukhaug et al. 2014, Martin-Ferrero 2014, Semere et al. 2015).…”
mentioning
confidence: 99%
“…However, considerable attention has been paid for the non-operative treatment of Dupuytren disease. Injectible collagenase is more efficient than surgical fasciotomy and has milder side effects, which leads to higher patient satisfaction [97,98]. Studies on the influence of CHCs on Dupuytren's cords and on Dupuytren's disease fibroblasts have demonstrated that clostridial collagenases can efficiently digest ECM of Dupuytren's disease cords without inducing significant cytotoxicity or structural damage to non-collagenous tissue elements [99,100].…”
Section: Collagenase As Debriding Agent In Wound Healingmentioning
confidence: 99%